Contribution of Educational Institutions in the Preservation of Traditional Culture Karawitan Java - Dzakia, Shinta Nur; Saputri, Indri Dewi; Sari, Rani Puspita; Hayati, Kulsum Nur (Jurusan PG-PAUD Universitas Halu Oleo,, 2024)
Culture as a state identity must always be preserved so that it remains alive and relevant for every generation of society. Indonesia has a variety of cultures, including traditional music on the island of Java, namely Karawitan Art. The process of cultural inheritance can be through educational institutions which are leading institutions that are in direct contact with the nation's generation. So this research was taken to describe the efforts made by educational institutions in contributing to preserving the traditional culture of karawitan art concretely. A study designed using a qualitative approach with a case study type . Data was obtained through observation, interviews and documentation. The informants are educators and trainers. The number of students is 26 children, all of whom participated in karawitan activities. This karawitan group is named